2020
DOI: 10.1002/jcla.23347
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of copy number variation by sequencing in fetuses with nuchal translucency thickening

Abstract: Objective Copy number variation sequencing (CNV‐seq) technique was used to analyze the genetic etiology of fetuses with increased nuchal translucency (NT). Methods A total of 139 women with gestational 11‐14 weeks whose fetuses were detected with increased NT (NT ≥ 2.5 mm) in our hospital from July 2016 to December 2018 were selected. Fetal specimens were performed for karyotyping analysis and CNV sequencing. Results According to the nuchal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…13,14 An increasing number of studies had shown that pathogenic copy number variations (pCNVs) account for a certain percentage of the fetuses in older pregnant women and with abnormal ultrasound. 15,16 Karyotype analysis is one of the main detection techniques for chromosomal abnormality. However, karyotype analysis has some limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 An increasing number of studies had shown that pathogenic copy number variations (pCNVs) account for a certain percentage of the fetuses in older pregnant women and with abnormal ultrasound. 15,16 Karyotype analysis is one of the main detection techniques for chromosomal abnormality. However, karyotype analysis has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 An increasing number of studies had shown that pathogenic copy number variations (pCNVs) account for a certain percentage of the fetuses in older pregnant women and with abnormal ultrasound. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Since CNV-seq was rst reported in 2009 that it could be used for accurate analysis of chromosomal copy number variation [22], more and more studies have proved that CNV-seq is feasible to improve the detection of chromosomal abnormality and may serve as a supplement for conventional karyotype analysis during the prenatal diagnosis [21][22][23]. However, the usefulness and incremental diagnostic yield of CNV-seq compared to standard karyotyping in fetuses with SUA remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Through whole genome low-coverage sequencing, CNV-seq is able to detect genetic aberrations, including chromosome aneuploidies and CNVs larger than 100 kb 8 . Combined with the advantages of using small amounts of genomic DNA and detecting low-level mosaicism, CNV-seq has been used increasingly widely for prenatal diagnosis 9 12 . However, due to its low sequencing depth, CNV-seq cannot detect balanced karyotypic changes and polyploidies such as 69, XXX 8 .…”
Section: Introductionmentioning
confidence: 99%